Extensive reading online: an overview and evaluation - Sun, YC (My University, 2003)
This study reports on the design and implementation of a reading program - Extensive Reading Online (ERO) - that aims to offer an online reading platform featuring specific needs for EFL learners in Taiwan. The system includes both teacher and student interfaces. Several reading aids are integrated into the system, such as concordancer help, stage-by-stage reading strategy training, and text annotation functions. ERO was integrated into a college level reading class. Results show that students held a positive attitude toward the reading system. Some recommendations for future improvement are also discussed.
Keywords: concordancer; extensive reading; english; ESL; reading strategies; undergraduate; world-wide web